Vital resonances encountering film with Varda, Haneke and Nancy - Hardy, Francesca Minnie (Edinburgh University Press, 2021)
Establishes resonance as a critical and conceptual paradigm for film analysis bringing together, for the first time, the work of three of the leading figures in European film: Agnès Varda, Michael Haneke and Jean-Luc Nancy.
Keywords: Varda, Agnès, -- 1928-2019 -- Criticism and interpretation.; Haneke, Michael, -- 1942- -- Criticism and interpretation.; Nancy, Jean-Luc.; Haneke, Michael, -- 1942-; Nancy, Jean-Luc; Varda, Agnès, -- 1928-2019; Film criticism.; Motion pictures -- Philosophy.; Critique cinématographique.; Cinéma -- Philosophie.; Film criticism; Motion pictures -- Philosophy; Criticism, interpretation, etc.